Machine Learning-based Derivation and External Validation of a Tool to Predict Death and Development of Organ Failure in Hospitalized Patients with COVID-19 - Xu, Yixi; Trivedi, Anusua; Becker, Nicholas; Blazes, Marian; Lavista Ferres, Juan M.; Lee, Dr. Aaron; Liles, W; Bhatraju, Dr. Pavan (Scientific Reports, 2022)
COVID-19 mortality risk stratification tools could improve care, inform accurate and rapid triage decisions, and guide family discussions regarding goals of care. A minority of COVID-19 prognostic tools have been tested in external cohorts. Our objective was to compare machine learning algorithms and develop a tool for predicting subsequent clinical outcomes in COVID-19.